La medición del desempleo en Andalucía. - Aracil Fernández, Mª José; Gómez García, Francisco (Cuadernos de Estudios Empresariales, 2000)
The disproportionately high unemployment figures in Andalusia show tbe magnitude of the issue in our community. Nevertheless, reliability of statistics has been quite often questioned --were figures right, scrious social turmoil would bave resulted. Ibis article seeks to examine that argument for the Andalusian labour market. In the first place, we conduct an overalí valuation of statistical sources aimed at measuring unemployment available in Spain --mainly EPA and jobless registered at INEM. Ihen we analyze the evolution of estimated unemployment (EPA) 13 M a José A mcii Fernández y Fmnciyco Gómez Garría La medición del desempleo en Andalucía and registered unemployment (INEM) in Andalusia, cross-checking total figures, as well as its sector and sex composition. Finally, based on previous sections, sorne comments put the issue in due perspective. 1.